The Determination of Haemostasis Value in Relation to Potential Blood Leaf Leaves Filtrate (Excoecaria cochinchinensis L) as the External Medicine for Skin Wound of White Rat (Rattus norvegicus) - Zaetun, Siti; Srigede, Lalu (Indonesian Journal of Medicine, 2020)
Background: Plants are currently used as medicine, i.e. medicinal plants. Medicinal plants consist of many chemical compounds, especially bioactive substances. One of them is Sambang Darah (Excoecaria cochinchinensis). Sambang Darah have so many benefits which usually applied in vulnus combutio. This study aimed to determine value of haemostasis after applied Sambang Darah leaves in white rat skins (Rattus norvegicus).Subjects and Method: This was a true experimental study with post test only control group design. This study conducted at Mata-ram University, West Nusa Tenggara, Indo-nesia, from April to October 2017. A total sam-ple of 16 white rats was selected for this study. The dependent variable in this study was the value of haemostasis and the independent vari-able was filtrate of Sambang Darah leaves. The data were analyzed using Man Whitney test.Results: The average level of bleeding time was 3.76 minutes for the control group and 2.58 minutes for test group. The average level of clotting time were 2.20 minutes for control group and 1.36 minutes test group. The number of platelet was 277,000/uL for the control group and 221,000/uL for test group. APTT level was25.06 second for the control group and there was no clot in test group. PT level was 13.95 second for the control group and there was no clot in test group. TT levels was 18.2 second for the control group and there was no clot in test group. And the last, D Dimer level was 0.1 mg/l for the control group and there was no clot in test group. The statistical analysis showed p ≤0.001.Conclusion: Filtrat of sambang darah leaves can be applied as medicine for external wounds but it can not be applied in koagulasi test.Keywords: Haemostasis value, blood leaf filtrate (Excoecaria cochinchinensis L)Correspondence: Siti Zaetun.Program Study of Health Analyst, School of Health Polytechnic, Ministry of Health, Mataram. Jl. Prabu Rangkasari, Dasan Cermen, Sandubaya, Mataram, West Nusa Tenggara. Email: miraigan@yahoo.co.id. Mo-bile: 081803630063.Indonesian Journal of Medicine (2020), 5(1): 10-16https://doi.org/10.26911/theijmed.2020.05.01.02